Anatomy of the ribs and management of their fractures as viewed by Avicenna (980-1037 AD) : Anatomija i liječenje prijeloma rebara u Aviceninu prikazu - Paydar, Shahram (Array, 2019)
Method: We reviewed Avicenna’s Canon and his viewpoints on the anatomy of the rib bones and their fractures and compared it with conventional medicine. Result: He described the anatomy of the ribs; he explained the effectiveness of their structure in the protection of vital organs. He also suggested some methods for the management of rib fractures, such as using vacuum at the fracture site or open surgery in case of complications. Conclusion: Avicenna’s point of view on the approach toward rib fractures had some similarities and differences with conventional practice. Some of his suggestions could be taken into account.